Prevalence, Lesion Characteristics, Risk Factors of Scabies Transmission in Cats (Felis catus) at Go Pet Care Animal Clinic (2020-2022) - Dara, Sarah Azzahra Dwi; Fauziah, Nisa; Khairani, Shafia (Universitas Airlangga, 2025)
The COVID-19 pandemic (2019-2021) resulted in a surge in pet adoptions, potentially elevating the risk of various diseases in domestic cats, including scabies. Scabies, a highly contagious dermatological condition, is primarily caused by parasitic mites such as Notoedres cati and Sarcoptes scabiei. This study aimed to investigate the prevalence, clinical manifestations, and associated risk factors of scabies in domestic cats at Go Pet Care Animal Clinic in West Bandung Regency over the period from 2020 to 2022. Utilizing a cross-sectional study design, secondary data were extracted from medical records and analyzed using Microsoft Excel and SPSS version 29.0.1.0. A chi-square test was performed with a 95% confidence level (α = 0.05) to assess the statistical significance of the findings. Out of 71 cats diagnosed with scabies, the highest incidence was observed in cats under one year of age (kittens), long-haired breeds, and females. The prevalence of scabies showed a significant increase, rising from 2% to 11.2% over the study period. Common clinical manifestations included alopecia and crusting. Statistical analysis revealed that age was a significant risk factor influencing the prevalence of scabies. These findings underscore the need for heightened awareness and preventive measures for scabies, particularly in younger and long-haired cats.